Imigrantes e nacionais: um estudo sobre as relações sociais em sala de aula - Soares, Cybele de Faria e (2015)
When new subjects appear within the classroom space, it is a prolific time to discuss the pedagogical practice through their demands. The emergence of immigrants in schools raises various questions and this research intends to discuss the social relations between nationals and immigrants in the classroom and the their meanings in the integration and constitution of the immigrant self-image, in the Elementary Education II of a private school in the city of São Paulo. To investigate the dynamics promoted by teachers, the relationships between students and the speeches, it was necessary a study contemplating an intensive observation, interviews with school players and document analysis. The fieldwork revealed that some immigrant students interact with restrictions in the classroom and gather in groups of the same nationality. The justification for this fact, found in the literature review, that teachers do not have sensitivity to understand the phenomenon of migration and its consequences in the identities of the students was insufficient to understand that school's reality. Conflicts, disputes and ideas that nationals students sustain on immigration and immigrants interfere in their relationship with them and can shape their images about themselves. We elected theoretical interlocutors as SAYAD (1998, 2010) to explain, based on sociology, the complexity of the migration phenomenon, ELIAS (2000) to understand the disputes between groups that, in the struggle for social spaces, humiliate and attribute low human value to newly arrived immigrants who, in turn, absorb the stigma that is alleged against them, lowering them self esteem. The stigmatization suffered by immigrant groups relied on GOFFMAN (2008) to be better understood. It is worth noting that the choice of an elite school with a large group of immigrants, Peruvian and Chinese, was strategic in order to understand school dynamics